Myristoylated Eepd1 Enhances Lipolysis and Thermogenesis through PKA Activation to Combat Obesity - Suzhen Chen; Yanping Wang; Qian Zhou; Qiqi Qian; Quanxin Jiang; Chuchu Liu; Yan Liu; Peihui Zhou; Jie Xiong; Yao Zhang; Ning Wang; Yang Emma Li; et al. (Nature Communications)
Abstract Middle-aged obesity, characterized by excessive fat accumulation and systemic energy imbalance, often precedes various health complications. Recent research has unveiled a surprising link between DNA damage response and energy metabolism. Here, we explore the role of Eepd1, a DNA repair enzyme, in regulating adipose tissue function and obesity onset. Eepd1 is primarily expressed in adipose tissue, where its downregulation or deletion accelerates obesity development. We show that Eepd1 ablation hinders PKA activation, thereby inhibiting lipolysis and thermogenesis in adipose tissue. Notably, cold exposure enhances Eepd1’s myristoylation, facilitating its anchorage to adipocyte membranes and subsequent activation of PKA, while a mutation at the myristoylation site of Eepd1 disrupts this process. Moreover, individuals with obesity exhibit reduced Eepd1 expression. Pharmacological restoration of Eepd1 with Retigabine dihydrochloride effectively mitigates obesity. This study reveals Eepd1’s unexpected role in promoting adipose lipolysis and thermogenesis, underscoring its potential as a promising therapeutic target to combat obesity.